Social Life And Practices Of Naga People And Its Philosophical Implication - JEUTI DEVI; SAMIKSHYA GOHAIN (Elementary Education Online, 2020)
Naga society is patriarchal in nature, in which man is the head of the family. Though Nagaland is the hometown for all the Nagas, but they are staying in different parts of India because of education, job and business. Naga society is casteless, classless society, unlike other Indian tribal societies. Though Nagas are patriarchal in nature, but women are not neglected unlike the ancient Hindu society. All the Nagas are hardworking, brave, kind, innocent, and nature lover. The social life of the Naga people is very unique. They love to live together and work together. So, this paper is an attempt to focus the social life of the Nagas and also to highlight the philosophical implication of their beliefs which are related with their social life.